2014
DOI: 10.1183/09059180.00008313
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in pregnancy: a hit for two

Abstract: Asthma commonly occurs in pregnant females, and recent data have outlined the risks of adverse perinatal outcomes among this population. There is an increased risk of low birth weight and small for gestational age, particularly among females with moderate-to-severe asthma and exacerbations during pregnancy. There is also an increased risk of preterm birth, especially with oral steroid use, a small but statistically significant increased risk of congenital malformations, particularly of cleft lip with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
0
34
0
5
Order By: Relevance
“…Childhood asthma may be more strongly associated with neural tube than non‐neural tube defects. The findings merit follow‐up in future mechanistic studies as asthma is common (Murphy & Schatz, ; Sears et al, ), and central nervous system defects place significant pressure on health care and families. Further investigation of these patterns may provide insight into the pathology of both asthma and central nervous system defects, perhaps leading to therapeutic or preventive approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood asthma may be more strongly associated with neural tube than non‐neural tube defects. The findings merit follow‐up in future mechanistic studies as asthma is common (Murphy & Schatz, ; Sears et al, ), and central nervous system defects place significant pressure on health care and families. Further investigation of these patterns may provide insight into the pathology of both asthma and central nervous system defects, perhaps leading to therapeutic or preventive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies suggest that asthma is linked with birth defects in offspring (Blais, Kettani, Elftouh, & Forget, ; Lin et al, ). Asthma affects up to 12% of pregnant women (Murphy & Schatz, ; Namazy et al, ), but the association with central nervous system defects in offspring receives relatively little attention compared with other congenital anomalies. There is conflicting evidence that asthma during pregnancy is associated with nervous system defects (Blais et al, ; Garne et al, ; Garne et al, ; Lin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is one of the most common diseases complicating pregnancy and its prevalence among pregnant women is increasing. (66) The complex nature of the developmental processes that can be affected by the prenatal asthma milieu, suggests increased risk for asthma among offspring is not simply a result of genetic predisposition but likely includes in utero transfer of environmental risk. Moreover, active asthma in pregnancy has been linked to a number of adverse outcomes for the developing child, in addition to asthma development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that about 65% of patients have poor control of asthma during pregnancy, inhaler technology is not correct in 64.4% of cases, only 38% of patients know the difference between asthma reliever and controlled medications, 12.7% of patients receive a written asthma action plan, 17% of patients have spirometry in the past 5 years, and 3.8% of them have peak expiratory flow meter at home [5]. Studies have shown that maternal asthma increases the risk for adverse complications in fetuses and mothers, including SGA (small for gestational age), LBW (low birth weight), congenital malformations (cleft lip or cleft palate), increased perinatal mortality, PB (premature birth), maternal preeclampsia, gestational hypertension, gestational diabetes, prenatal hemorrhage, caesarean section, urinary tract infection, excessive amniotic fluid, and premature rupture of membranes, especially for those patients with severe or uncontrolled asthma during pregnancy [6,7].…”
Section: Introductionmentioning
confidence: 99%